2018
DOI: 10.2147/rmhp.s151902
|View full text |Cite
|
Sign up to set email alerts
|

Changing patient safety culture in China: a case study of an experimental Chinese hospital from a comparative perspective

Abstract: BackgroundThe World Health Organization highlights that patient safety interventions are not lacking but that the local context affects their successful implementation. Increasing attention is being paid to patient safety in Mainland China, yet few studies focus on patient safety in organizations with mixed cultures. This paper evaluates the current patient safety culture in an experimental Chinese hospital with a Hong Kong hospital management culture, and it aims to explore the application of Hong Kong’s pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 28 publications
(50 reference statements)
2
13
0
Order By: Relevance
“…Interviewees expressed they would choose to be silent even when they had different opinions than their superiors. They feared punishment if they were to disagree with their superior's decisions, which is known as 'blame culture' (Jeppsson, Ostergren, & Hagstrom, 2003;Sakyi, Awoonor-Williams, & Adzei, 2011;Xu et al, 2018). In our study, nurses complained that some ED Clique Culture • Sometimes our nurses are very distressed.…”
Section: Discussionmentioning
confidence: 69%
“…Interviewees expressed they would choose to be silent even when they had different opinions than their superiors. They feared punishment if they were to disagree with their superior's decisions, which is known as 'blame culture' (Jeppsson, Ostergren, & Hagstrom, 2003;Sakyi, Awoonor-Williams, & Adzei, 2011;Xu et al, 2018). In our study, nurses complained that some ED Clique Culture • Sometimes our nurses are very distressed.…”
Section: Discussionmentioning
confidence: 69%
“…Mixed results are also found in terms of education level and age. Staff with a degree higher than bachelor score "communication openness" (42) and "teamwork across units" (46) significantly higher but "teamwork climate" significantly lower than those with an education level lower than bachelor (35,45). Staff younger than 25 years report significantly higher scores for "teamwork climate" than those older than 50 years in one study (45) but the opposite is found in another study (35).…”
Section: Relationship Between Inputs and Processesmentioning
confidence: 88%
“…The relationship between the input "profession" and team processes is inconclusive, although profession is researched the most in these studies. Two HSOPSC studies show that nurses score "communication openness" significantly higher than doctors (37,42), while two other HSOPSC studies find no significant differences between the ratings of doctors and nurses (36,46). Two SAQ studies find that doctors evaluate "teamwork climate" significantly more positively than nurses (35,45).…”
Section: Relationship Between Inputs and Processesmentioning
confidence: 99%
See 2 more Smart Citations